New records of ants of the Colombian Caribbean, including taxonomic keys for Acanthoponera, Heteroponera and Platythyrea - GUERRERO-F., ROBERTO J.; OLIVERO-G., DEIVER Y. (Revista Colombiana de Entomología, 2007)
Four species of poneromorpha ants are registered for the first time for the Colombian Caribbean, Platythyrea pilosula, Platythyrea prizo, Acanthoponera mucronata, and Heteroponera angulata. The latter is a new record for Colombia. Keys to the Colombian Heteroponerinae species as well as keys to the Colombian species of the Platythyrea (Ponerinae) are given.